Penerapan Mentoring dengan Shared Vision dan Team Learning untuk Meningkatkan Kedisiplinan Guru di SD Kristen XYZ Sentani - Reza Kaligis; Budi Haryono; Amy Iwani (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Teacher discipline is essential in fostering a productive and collaborative learning environment. Low administrative discipline and restricted teacher collaboration at Sentani's XYZ Christian Elementary School have become key barriers to attaining the school's vision and enhancing instructional quality. This study seeks to improve teacher discipline by combining a mentoring method with the principles of Shared Vision and Team Learning. School Action Research, based on the Kemmis and McTaggart spiral model, was utilized in two cycles to study five instructors who had administrative discipline difficulties. Data were gathered by observation, interviews, questionnaires, and document analysis, then analyzed using descriptive quantitative and qualitative approaches. The results show a considerable improvement in administrative document submission timeliness and instructor attendance at school activities. By the end of the second cycle, 80% of teachers had delivered their documents on time, and the average collaboration score had grown by more than 20% from the beginning. The implementation of Shared Vision generated a sense of responsibility for the school's vision, whereas Team Learning increased teacher collaboration frequency and quality. Structured mentoring was successful in changing instructors' mindsets and work behaviors. The study indicates that mentorship based on Shared Vision and Team Learning can promote a more disciplined, collaborative, and responsible workplace culture that is consistent with Christian principles and the school's strategic direction.